1999
DOI: 10.1073/pnas.96.7.3928
|View full text |Cite
|
Sign up to set email alerts
|

The FEZ1 gene at chromosome 8p22 encodes a leucine-zipper protein, and its expression is altered in multiple human tumors

Abstract: Alterations of human chromosome 8p occur frequently in many tumors. We identified a 1.5-Mb common region of allelic loss on 8p22 by allelotype analysis. cDNA selection allowed isolation of several genes, including FEZ1. The predicted Fez1 protein contained a leucine-zipper region with similarity to the DNA-binding domain of the cAMPresponsive activating-transcription factor 5. RNA blot analysis revealed that FEZ1 gene expression was undetectable in more than 60% of epithelial tumors. Mutations were found in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 34 publications
0
141
0
2
Order By: Relevance
“…The latter cell line has been shown by Northern blot analysis not to express the full length LZTS1 mRNA (Ishii et al, 1999). The results of these experiments are shown in Figure 5a.…”
Section: Different Effects Of Lzts1 Over-expression On Human Prostatementioning
confidence: 87%
See 3 more Smart Citations
“…The latter cell line has been shown by Northern blot analysis not to express the full length LZTS1 mRNA (Ishii et al, 1999). The results of these experiments are shown in Figure 5a.…”
Section: Different Effects Of Lzts1 Over-expression On Human Prostatementioning
confidence: 87%
“…Based on the published pattern of expression and the function (when known) of these genes, all except LZTS1 were excluded from further study as potential TSGs. Even though the function of the LZTS1 gene is unknown, it was previously identi®ed as a candidate TSG on the basis of its di erential expression in tumor and normal tissues in several types of cancers (Ishii et al, 1999). It was isolated originally from a YAC (859A7) that overlaps with YACs 911G7 and 739B2.…”
Section: Identification Of Lzts1 As a Potential Tsg In The Yac Overlamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 8p might harbor one or more tumorsuppressor genes that are important in progression, especially the metastasis of cancers, including HCC (Nihei et al, 2002). Several candidate tumor-suppressor genes have been identified from 8p, including DLC-1 (8p21.3-22) (Yuan et al, 1998), FEZ1 (8p22) (Ishii et al, 1999), liverrelated putative tumor suppressor gene (8p23) (Liao et al, 2000), PCM1 (which encodes a centrosomal protein), and DUSP4/MKP-2 (which encodes a MAP kinase phosphatase) (Armes et al, 2004). However, alterations in these genes may occur as an early event in the development of cancers, and their association with metastasis has not been confirmed (Park et al, 2002), even though one very recent study indicated that FEZ1 may serve as a novel prognostic indicator for lung cancer (Nonaka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%